2017
DOI: 10.1002/ca.22936
|View full text |Cite
|
Sign up to set email alerts
|

Description and ultrasound targeting of the origin of the suprascapular nerve

Abstract: Anatomical variations in the suprascapular nerve (SSN) and its depth in the suprascapular notch can make it difficult to target with ultrasonography (US). One alternative could be a proximal approach to the SSN, if US provides a reliable description of its origin (orSSN). The primary objective of this study was to demonstrate that US can reliably locate the orSSN. The secondary objective was to describe the features of the proximal SSN. Seventy brachial plexuses (BPs) from 30 healthy volunteers (60 BPs) and 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…We confirmed these findings; however the mean depth of the SSN (1.5 cm (range, 0.6–2.3 cm)) in our study was approximately double that identified by Faruch et al (). Despite this increased depth, we were able to achieve 100% accuracy of US‐guided ink marking of the proximal SSN, confirming that dynamic analysis of the proximal SSN is accurate and reproducible (Laumonerie et al). The injection needle was consistently located distal to the orSSN in an effort to increase the distance of the anesthetic fluid from the PN while maintaining the utility of the orSSN as an anatomic landmark (Table ).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…We confirmed these findings; however the mean depth of the SSN (1.5 cm (range, 0.6–2.3 cm)) in our study was approximately double that identified by Faruch et al (). Despite this increased depth, we were able to achieve 100% accuracy of US‐guided ink marking of the proximal SSN, confirming that dynamic analysis of the proximal SSN is accurate and reproducible (Laumonerie et al). The injection needle was consistently located distal to the orSSN in an effort to increase the distance of the anesthetic fluid from the PN while maintaining the utility of the orSSN as an anatomic landmark (Table ).…”
Section: Discussionsupporting
confidence: 77%
“…We advocate for the use of the orSSN as a landmark for US‐guided regional anesthesia of the supraclavicular portion of the SSN. It is important to note, however, that the injections in the present study were performed by a highly experienced operator (Faruch et al ; Laumonerie et al). Due to this, we recommend that the technique and interpretation of BP anatomy on US be mastered in order to obtain satisfactory results (Schneider‐Kolsky et al ; Chan et al 2011; Lapègue et al 2014; Rothe et al ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The brachial plexus continues to be of significant clinical interest [8][9][10][11][12][13] and thus our current knowledge of this structure was begun by the works of da Vinci in the fifteenth century. …”
Section: Discussionmentioning
confidence: 99%